2017
DOI: 10.1177/0954405417718591
|View full text |Cite
|
Sign up to set email alerts
|

Micro-electrical discharge machining of difficult-to-machine materials: A review

Abstract: Electrical discharge machining has emerged as one of the most accepted non-traditional machining methods that have the capability of attaining complex shapes and better feature size in difficult-to-machine materials. In this article, an advanced review of conventional electrical discharge machining and micro–electrical discharge machining of difficult-to-machine materials, such as nickel and its alloys, titanium alloys, stainless steel (SUS 304) and advanced ceramics, has been presented. The review begins with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
45
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 89 publications
0
45
0
2
Order By: Relevance
“…The electrical energy was converted to thermal energy by means of a series of discrete electrical discharges between the electrode and workpiece immersed in dielectric medium. 79 Due to the sparking effect, the energy distributed over all the regions of the surface. 10,11 During EDM modification procedures, the discharge characteristics and energy distribution of the working medium play an important role in the microstructure and properties modification of strengthened layer.…”
Section: Introductionmentioning
confidence: 99%
“…The electrical energy was converted to thermal energy by means of a series of discrete electrical discharges between the electrode and workpiece immersed in dielectric medium. 79 Due to the sparking effect, the energy distributed over all the regions of the surface. 10,11 During EDM modification procedures, the discharge characteristics and energy distribution of the working medium play an important role in the microstructure and properties modification of strengthened layer.…”
Section: Introductionmentioning
confidence: 99%
“…Muthuramalingam 32 analyzed the influence of a modified pulse energy generator system on performance measures and observed that peak current is a significant factor in determining white layer formation in the EDM process. An advanced review of conventional- and micro-EDM of difficult-to-machine materials, such as nickel and its alloys, titanium alloys, stainless steel (SUS 304), and advanced ceramics, has been presented by Prakash et al 33 Rajeswari and Shunmugam 34 presented a comparative study on the performance of the classical EDM and powder-mixed and ultrasonic-assisted rough die-sinking EDM based on pulse characteristics. Mascaraque-Ramirez and Franco 35 worked on different methods for experimental analysis of surface integrity in die-sinking and suggested that the crater diameter can be adopted as a better indicator to characterize the surface quality in EDM.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, micro-electrical discharge machining (EDM) and micro-electrochemical machining (ECM) have been have been extensively researched for the micromachining of Inconel 718. 7,8 However, these technologies are limited by the challenges of severe electrode wear, low machining speed, and increased cost. Ultrasonic-assisted hybrid machining (USM) is considered as an alternative process for the fabrication of Inconel 718.…”
Section: Introductionmentioning
confidence: 99%